YUGOSLAV CONFLICT: EXTERNAL EFFORTS FOR PEACE IN BOSNIA AND HERZEGOVINA - Azimzhan Akbota (Foundations and Trends in Modern Learning, 2023)
The article examines the process of participation of external actors in the settlement of the conflict in Bosnia and Herzegovina (BaH) in 1992-1995, which was the most complex of all the conflicts that arose as a result of the destruction of the Socialist Federal Republic of Yugoslavia (SFRY). The violent confrontation between the three main ethnic groups of BaH (Bosnian Serbs, Bosnian Muslims and Bosnian Croats) deprived the post-Yugoslav state of the opportunity to find internal sources of exit from the crisis. At the initial stage of its escalation, until 1994, the role of conflict mediators were assumed by the European Community (EC), NATO and a number of international organizations, but their efforts were unsuccessful. The conflict in BaH required the search for new methods for the Yugoslav settlement, and with the intervention of the United States and the decision, with the consent of the United Nations Security Council, to use the military forces of the North Atlantic Alliance (NATO), it allowed Washington to put an end to the armed confrontation between the warring parties by force and to come to peace. The conflicting parties were forced to sit down at the negotiating table, as a result of which the Dayton Agreements were concluded, which changed the geopolitical situation in the post-Yugoslav space.